Characterization of the locomotor depression produced by an A(2)-selective adenosine agonist - Nikodijević, Olga (1990)
Adenosine analogs, such as N(6)-cyclohexyladenosine (CHA) that are selective for A(1)-adenosine receptors, and analogs, such as 5′-N-ethylcarboxamidoadenosine (NECA) that are active at both A(1) and A(2) receptors, cause a profound depression of locomotor activity in mice via a central mechanism. The depression is effectively reversed by non-selective adenosine antagonists such as theophylline. We report that 2-[(2-aminoethyl-amino)carbonylethylphenylethylamino]-5′-N-ethylcarboxamidoadenosine (APEC), an amine derivative of the A(2)-selective agonist, CGS21680, is a potent locomotor depressant in mice. The in vivo pharmacology is consistent with A(2)-selectivity at a central site of action. Two parameters indicative of locomotor activity, horizontal activity and total distance travelled, were measured using a computerized activity monitor. From dose-response curves it was found that APEC (ED(50) 16 μg/kg) is more potent than CHA (ED(50) 60 μg/kg) and less potent than NECA (ED(50) 2 μg/kg). The locomotor depression by APEC was reversible by theophylline, but not by the A(1)-selective antagonists 8-cyclopentyltheophylline (CPT) and 8-cyclopentyl-1,3-dipropyl-2-thioxanthine, nor by the peripheral antagonists 8-p-sulfophenyltheophylline (8-PST) and 1,3-dipropyl-8-p-sulfophenylxanthine. The locomotor activity depression elicited by NECA and CHA was reversed by A(1)-selective antagonists. These results suggest that the effects of APEC are due to stimulation of A(2) adenosine receptors in the brain.